Internal audit in Malaysian public sector: qualitative approach - Kudus, Norhidayu; Mustapha, Mazlina (American Scientific Publishers, 2017)
Internal audit is recognized as an important cornerstone in achieving good corporate governance. It should be considered as an integral part of an effective system of corporate governance. Among others, internal auditors play the role in evaluating the risk and monitoring the internal control system, as well as assisting the management in monitoring the effectiveness and efficiency of the operations. This paper examines the perception of the public agencies on the work done by their internal audit departments. Their perception on the audit itself, the improvements on operating efficiency after the audit, the effectiveness of the recommendations and the content of the report issued are sought. This study was conducted in one of the important ministries in Malaysia. This is a qualitative study where thirty public servants from ten government agencies were interviewed, ranging from supporting staff to managerial levels. The findings indicate that all the interviewees agree that their internal audit departments have contributed to the improvement of their internal control systems and it is an important department for their agencies. Among others, the internal audit department is seen as the party which encourages preventive actions, improves the transparency and the flow of their work processes and helps to bring positive changes to their agencies. However, they also highlight the constraints that they have to face in order to comply with the recommendations and rules and regulations in their agencies.